Cover Feature: Conformational Bias by a Removable Silyl Group: Construction of Bicyclo[n.3.1]alkenes by Ring Closing Metathesis (Chem. Eur. J. 10/2018). Issue 10 (19th December 2017) - Lin, Minggui; Cai, Pei‐Jun; Zeng, Zhixiong; Lin, Na; Shen, Yang; Tang, Bin; Li, Fan; Chen, Chen; Yu, Zhi‐Xiang; Zhang, Yandong
Abstract : A conformationally controlled ring‐closing metathesis through a removable silyl group has been developed for the synthesis of challenging bridged carbocycles. These include bicyclo[ n .3.1]alkenes, in particular, a set of highly strained bicyclo[5.3.1]alkenes. The utility of the methodology was demonstrated by a concise synthesis of the A‐B‐C ring skeleton of Taxol. More information can be found in the Communication by Z.‐X. Yu, Y. Zhang et al. onpage 2334 .